The Role of the School Principle Instructional Leadership on Teacher Professional Competence - Eki Anisa Putri; Riswandi Riswandi; Sowiyah Sowiyah; Riswanti Rini (Universitas Muhammadiyah Enrekang, 2023)
This article aims to analyze and describe the role of the school principle instructional leadership on teacher professional competence. The method of this article uses the literature study method, namely by collecting data or sources related to the topic raised. The findings can be concluded that the school are expected to contribute to realizing the role of the principal's instructional leadership. Based on the findings it can be concluded that instructional leadership or commonly called learning leadership, must be able to assume that schools will improve if the principal can set clear academic goals, motivate staff and students to work towards these goals, align progress, and align teaching and learning. learning activities to achieve these goals. Research shows that in line with the curriculum, methods that are appropriate to the characteristics and goals of students, evaluation, and supervision actions that are integrated with a sustainable system are indicators of the quality of the learning process.